Management of biogenic taste and odour: From source water, through treatment processes and distribution systems, to consumers. (1st December 2022) - Zhu, Jin; Stuetz, Richard M.; Hamilton, Lisa; Power, Kaye; Crosbie, Nicholas D.; Tamburic, Bojan
Abstract: Biogenic taste and odour (T&O) have become a global concern for water utilities, due to the increasing frequency of algal blooms and other microbial events arising from the combined effects of climate change and eutrophication. Microbially-produced T&O compounds impact source waters, drinking water treatment plants, and drinking water distribution systems. It is important to manage across the entire biogenic T&O pathway to identify key risk factors and devise strategies that will safeguard the quality of drinking water in a changing world, since the presence of T&O impacts consumer confidence in drinking water safety. This study provides a critical review of current knowledge on T&O-causing microbes and compounds for proactive management, including the identification of abiotic risk factors in source waters, a discussion on the effectiveness of existing T&O barriers in drinking water treatment plants, an analysis of risk factors for biofilm growth in water distribution systems, and an assessment of the impacts of T&O on consumers. The fate of biogenic T&O in drinking water systems is tracked from microbial production pathways, through the release of intracellular T&O by cell lysis, to the treatment of microbial cells and dissolved T&O. Based on current knowledge, five impactful research and management directions across the T&O pathway are recommended. Graphical abstract: Image 1 Highlights: Critical review of biogenic taste and odour in drinking water from source to tap. Improved detection and analysis of odorants beyond geosmin and MIB is required. Better understanding of microbes in source water can inform early warning systems. Flexible and responsive treatment solutions are needed for emerging odorants. Operationalised consumer data and better communication would benefit water managers.